Epilithic biofilms as a discriminating matrix for long-term and growing season pesticide contamination in the aquatic environment: Emphasis on glyphosate and metabolite AMPA - Fernandes, Gracieli; Aparicio, Virginia Carolina; De Geronimo, Eduardo; Prestes, Osmar Damian; Zanella, Renato; Ebling, Ederson; Bolzan Parisi, Pedro; Mollmann, Victor Hugo Dos Santos; Reichert, José Miguel; Dos Santos, Danilo Rheinheimer (Elsevier, 2023)
The indiscriminate use of pesticides represents high ecological risk in aquatic systems. Recently, the inclusion of epilithic biofilms as a reactive matrix has shown potential in diagnosing the health of water resources. The objective of this study was to use multiple matrices (water, suspended sediments, and biofilms) to discriminate contamination degrees in catchments with long and recent history of intensive pesticide use and to monitor growing season pesticides transfer to watercourses. Two catchments were monitored: one representative of “modern agriculture” in a subtropical environment, and another representative of recent agricultural expansion over the Pampa Biome in subtropical Brazil. Glyphosate and AMPA were accumulated in the biofilms and were detected at all sites and at all monitoring times, in concentrations ranging from 195 to 7673 μg kg−1 and from 225 to 4180 μg kg−1, respectively. Similarly, the fungicide tebuconazole has always been found in biofilms. The biofilms made it possible to discriminate the long-term history of pesticide use in the catchments and even to identify the influx pulses of pesticides immediately after their application to crops, which was not possible with active water sampling and even with suspended sediment monitoring. It is strongly recommended that, in regions with intensive cultivation of soybeans and other genetically modified crops, the presence of glyphosate and its metabolite AMPA be permanently monitored, a practice still very scarce in the literature.